Storm and stampede on the Chisholm - Collins, Hubert E. (Hubert Edwin), 1872-1932 (University of Nebraska Press, 1998)
In 1883 young Hubert Collins traveled the Chisholm Trail to a ranch in Indian Territory. For the next fifteen months he lived at the Red Fork Ranch on the banks of the Cimarron River at present-day Dover, Oklahoma. It was the boy.